2019
DOI: 10.3390/ijms20163876
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mesenchymal Stem Cells in Radiation-Induced Lung Fibrosis

Abstract: Radiation therapy is one of the most important treatment modalities for thoracic tumors. Despite significant advances in radiation techniques, radiation-induced lung injury (RILI) still occurs in up to 30% of patients undergoing thoracic radiotherapy, and therefore remains the main dose-limiting obstacle. RILI is a potentially lethal clinical complication of radiotherapy that has 2 main stages: an acute stage defined as radiation pneumonitis, and a late stage defined as radiation-induced lung fibrosis. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 202 publications
(382 reference statements)
0
63
0
1
Order By: Relevance
“…MSCs can successfully migrate towards the injured site in the lung upon irradiation and differentiate into distinct lung cell types, including AT I/II cells and endothelial cells. Preclinical studies reported that lung fibrosis can be modulated by administration of MSCs [195,196]. In these settings, adoptive transfer of MSCs did limit radiation-induced endothelial cell loss in the early phase after irradiation and promoted tissue repair through the secretion of superoxide dismutase 1 (SOD1) [197] and the anti-fibrotic factors hepatocyte growth factor (HGF) and prostaglandin E2 (PGE2) [198].…”
Section: Prevention Of Radiation-induced Lung Injurymentioning
confidence: 99%
“…MSCs can successfully migrate towards the injured site in the lung upon irradiation and differentiate into distinct lung cell types, including AT I/II cells and endothelial cells. Preclinical studies reported that lung fibrosis can be modulated by administration of MSCs [195,196]. In these settings, adoptive transfer of MSCs did limit radiation-induced endothelial cell loss in the early phase after irradiation and promoted tissue repair through the secretion of superoxide dismutase 1 (SOD1) [197] and the anti-fibrotic factors hepatocyte growth factor (HGF) and prostaglandin E2 (PGE2) [198].…”
Section: Prevention Of Radiation-induced Lung Injurymentioning
confidence: 99%
“…Fibrosis is the last stage of chronic inflammatory responses and is characterized by the excessive deposition of the extracellular matrix, leading to tissue dysfunction in the affected organs [25]. Accumulating evidence suggests that MSCs have great potential in the treatment of fibrosis due to their abilities to act on proinflammatory and profibrotic factors such as oxidative stress, the TGF-β signaling pathway, and hypoxia [26][27][28]. Consistent with previous studies, we found that diabetic mice appeared to have a thickening alveolar wall, increased expression of SMA, and a massive infiltration of leukocytes in the lung tissue, exhibiting an obvious fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning pulmonary tissues, increasing evidences support MSCs regenerative properties. Indeed, they were able to engraft and to differentiate into lung epithelial cells under experimental conditions such as irradiation, bleomycin, or LPS-induced injury [86][87][88]. A systematic review of seventeen studies on rodents models of bleomycin-induced pulmonary fibrosis, describes the beneficial effects of MSCs, mostly derived from bone marrow, in improving alveolar injury and in decreasing lung fibrosis and collagen content [86].…”
Section: Mesenchymal Stem Cells: Principal Characteristics and Regenementioning
confidence: 99%
“…Data arising out of MSCs-based clinical trials demonstrate the variability of the use of this therapy in terms of MSCs source, route, timing, and dosage of administration. As very recently reviewed by Zanoni M. et al [87], the lack of consensus on these parameters (route, timing and dosage) together with the paucity of standardized methods for MSCs harvesting, request further studies in order to include MSCs therapy in the clinical practice in the near future. Moreover, donor variance, senescence, cryopreservation, and sources are among the main variables that can affect cellular therapies based on MSCs [116,117].…”
Section: Mesenchymal Stem Cells In Lung Inflammationmentioning
confidence: 99%